Textbooks for Writing Play Scripts Based on Local Culture in Higher Education - Irma Suryani; Julisah Izar; Sovia Wulandari; Helty (Journal for Lesson and Learning Studies, 2025)
Playwriting instruction in higher education should be designed to develop students’ writing competence, creativity, and critical thinking through systematic and contextual learning processes. However, in practice, such instruction still faces challenges, particularly the limited availability of comprehensive, applicable, and locally grounded instructional materials. This study aims to analyze, test, and evaluate the development of a local culture–based playwriting textbook in improving students’ writing competence. The study employs a Research and Development method using the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The research subjects were students enrolled in a playwriting course, with data collected through interviews, expert validation questionnaires, practicality questionnaires, and learning outcome tests in the form of pre-tests and post-tests. The research instruments consisted of validation sheets for content, language, and presentation, as well as a playwriting skills test, while data were analyzed using quantitative descriptive analysis, N-gain analysis, and qualitative interpretation of feedback from validators and users. The results indicate a significant improvement in students’ playwriting ability after using the developed textbook, particularly in the aspects of structure and development of dramatic elements, and show that the textbook is highly practical and suitable for instructional use. The study concludes that the local culture–based playwriting textbook is effective in enhancing students’ writing competence, creativity, and contextual understanding, highlighting the importance of developing culturally grounded instructional materials in higher education literary learning.